2019
DOI: 10.1088/1742-6596/1364/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Construction Contract Project Comparison with PNPM Based Projects in Construction Projects (PPIP Project Implementation Study In Tuban District)

Abstract: The implementation of construction projects generally carried out in construction contracts results in community apathy because they are not actively involved in the planning, implementation and maintenance operations of construction projects. The government launched the National Community Empowerment Program (PNPM). One of the PNPM programs initiated was the Rural Infrastructure Development Program (PPIP). Election Implementation of a construction project using a construction contract or community empowerment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…This research chose this time period with the assumption that it could reflect traffic flow conditions on weekdays, weekends, and when activities occur. In the analysis of the Jalan Dhoho Plaza intersection in Kediri City, the main information obtained directly involved vehicle traffic volume, road geometry, speed, capacity, degree of saturation, and signal timing [15]. Traffic volume was collected through manual surveys based on the 1997 MKJI vehicle classification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research chose this time period with the assumption that it could reflect traffic flow conditions on weekdays, weekends, and when activities occur. In the analysis of the Jalan Dhoho Plaza intersection in Kediri City, the main information obtained directly involved vehicle traffic volume, road geometry, speed, capacity, degree of saturation, and signal timing [15]. Traffic volume was collected through manual surveys based on the 1997 MKJI vehicle classification.…”
Section: Methodsmentioning
confidence: 99%
“…These factors include grade, vehicle composition, turning traffic maneuvers, pedestrian activity, and parked vehicles. Determination of the amount of Saturated Current is carried out using the following formula: 𝑆𝑜 = 600 × 𝑊𝑒 (2) Information: We = Entrance width of an Approach Intersection Saturated Flow (S) is the maximum capacity before congestion occurs [15]. The S value is calculated from the vehicle volume and a certain time duration with a formula involving basic saturation current (So), standard saturation current (with adjustment factor F), and a set of previously established ideal conditions.…”
Section: The Formulas Used Are As Follows: 1 Traffic Volumementioning
confidence: 99%
“…On the one hand, some teachers indicated that they left time in class for students to solve exercises, trying to favor autonomous and cooperative learning, which allows students to develop interaction skills for professional practice [17]. The approach to professional practice is also favored in project-based learning [46], a methodology that some teachers also followed in the group projects that they requested. On the other hand, several teachers used the flipped classroom for the explanation of some theoretical concepts, so that students had to learn and to understand the concepts before the class [47].…”
Section: Plos Onementioning
confidence: 99%